Effect of fiber breakage position on the mechanical performance of unidirectional carbon fiber/epoxy composites - Ma Yan (De Gruyter, 2021)
Fiber breakage is one of the most negative factors that affect the mechanical performance of unidirectional carbon-fiber (CF)-reinforced composites. In the present study, unidirectional CF-reinforced epoxy (CF/epoxy) laminates with and without fiber breakages located in different layers were manufactured from prepreg via hot compression. The static and cyclic flexural mechanical properties of the unidirectional CF/epoxy laminates were determined through static and low-cycle three-point bending tests. Flexural behavior was observed by using optical microscopy to discuss the failure behavior of the unidirectional CF/epoxy laminates. Results indicated that fiber breakages in different layers led to the static and cyclic mechanical degradation of the unidirectional CF/epoxy laminates. Moreover, fiber breakages in the tension side displayed higher flexural strength and better cyclic performance than those in the compression side.